2019
DOI: 10.47176/mjiri.33.19
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and self-esteem in sexual violence victims

Abstract: Social support plays an important role on physical and psychological health of sexual violence victims. Social support levels have also been observed to be associated with selfesteem. →What this article adds:Majority of female victims of sexual violence reported lower social support in their life but only friend's support had positive effect on their self-esteem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…While not studied as extensively as risk factors, resilience, and protective factors (those that buffer against negative outcomes) in recovery related to sexual assault have also been studied [ 25 , 61 , 62 ]. Among the general population, social support has been identified as a key protective factor in the prevention of sexual assault [ 62 ]. After an assault, social support, especially from friends, relatives, and the community are associated with better outcomes [ 25 , 61 , 65 ].…”
Section: The Fhort’s Resilience and Transcendence: Relational And Spi...mentioning
confidence: 99%
“…While not studied as extensively as risk factors, resilience, and protective factors (those that buffer against negative outcomes) in recovery related to sexual assault have also been studied [ 25 , 61 , 62 ]. Among the general population, social support has been identified as a key protective factor in the prevention of sexual assault [ 62 ]. After an assault, social support, especially from friends, relatives, and the community are associated with better outcomes [ 25 , 61 , 65 ].…”
Section: The Fhort’s Resilience and Transcendence: Relational And Spi...mentioning
confidence: 99%
“…The main objective of an online support group is to help its members overcome life stresses through social support, while perceived community privileges have a stronger effect in identifying groups than perceived external independence (Chiu et al, 2006). Women who experience sexual violence and receive social support are reported to have higher self-esteem, positively impacting their health (Shahali et al, 2010). In Golding, Wilsnack, and Cooper's (2002) study, social support was shown as having a protective effect against psychological disorders in victims of sexual violence, especially because victims seem to get less support than non-victims (Mason et al, 2009).…”
Section: Social Support Among Victims In Online Social Movementsmentioning
confidence: 99%
“…Communications and relationships that support and assist victims of sexual violence, needed to manage a violent situation, are referred as social support and play an important role in the physical and mental health of victims of sexual violence (Shahali et al, 2010). Although victims seem to receive less social support from non-victims, any kind of positive social support might have a protective effect on the psychological symptoms of sexual violence survivors (Mason et al, 2009).…”
Section: Introductionmentioning
confidence: 99%